Strategies for small dairy farmers to be profitable and competitive in the future - B. Cropp (Kansas Agricultural Experiment Station Research Reports, 1994)
Profitable dairying will not become any easier in the future. Farm level milk prices will continue to be volatile. The government will not provide additional price or income support to dairies. Long-run milk prices will be either flat or perhaps even trending slightly lower. Average annual milk prices will be in the range of 12.00 to 13.25 per hundredweight. Dairy producers must be able to generate adequate net income at these milk price levels. Smaller dairy operators need to find means of being cost competitive with the larger operators. Without question, smaller producers can be profitable in the decade ahead with proper changes. Not all profitable dairy operations will be those with at least 300 milk cows. There will be very profitable herds with 40, 50, 75, 100, and 150 cows. Even smaller herds will exist with substantial off-farm income or income from other farming enterprises.; Dairy Day, 1994, Kansas State University, Manhattan, KS, 1994;
Keywords: Dairy Day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-141-S; Report of progress (Kansas Agricultural Experiment Station); 716; Small farms; Herd size; Profitable; Costs; Milk Prices